Transnational migration entrepreneurship during a crisis: Immediate response to challenges and opportunities emerging through the COVID‐19 pandemic. (8th March 2022) - Harima, Aki
Abstract: The COVID‐19 pandemic has affected transnational migrant entrepreneurs due to deglobalization. It has limited their cross‐border mobility as well as collapsed the international value chain; their multiple embeddedness, which requires them to cope with two or more contexts; and the nature of transnational businesses, which are often more vulnerable than others. While entrepreneurship scholars have rapidly responded to the pandemic, its impact on this specific type of entrepreneur has not been investigated. This exploratory, interview‐based study identified three patterns of the entrepreneurial response of transnational migrant entrepreneurs to the pandemic: (1) balancing between multiple institutions, (2) mobilizing transnational social capital, and (3) adapting transnational value creation. Furthermore, this study identified factors on the individual, network, and macro levels that influence transnational migrants' entrepreneurial response to the pandemic. This study's findings revealed how entrepreneurs leverage cognitive flexibility and resource advantages from their multiple embeddedness to mitigate the adverse situation, find alternative strategic orientations, and explore and exploit emerging opportunities during the pandemic. The results of this study contribute to the emerging scholarly discussions on entrepreneurship under the COVID‐19 pandemic by elaborating on the unique contexts and entrepreneurial agents as well as add value to the literature on transnational migrant entrepreneurs by exploring their crisis response.